Far Lateral Intervertebral Disc Extrusion (IVDE) in a Dog: Sequestrectomy as a Potential Surgical Option - Ko, Seongju; Heung Myong Woo; Kihoon Kim; Kim, Junhyung (Acta Scientiae Veterinariae, 2026)
Background: Far lateral intervertebral disc extrusion (IVDE) is rare and poses diagnostic and therapeutic challenges in veterinary medicine. Although surgical techniques such as hemilaminectomy are widely used, they often require bone drilling, which may increase the risk of spinal instability and prolong operative time. In human medicine, sequestrectomy - removal of only the extruded disc without bone drilling - has demonstrated favorable outcomes in terms of recovery and pain management. However, this technique has not been previously reported or evaluated in veterinary patients. This case report introduces sequestrectomy for far lateral IVDE in a dog and describes its clinical outcome. Case: A 9-year-old, male castrated Coton de Tulear (chondrodystrophic dog breed) presented with a 5-month history of right hindlimb lameness and a prior history of cervical IVDD. Neurological examination revealed severe pain on palpation of the right L6-L7 region, with no other neurological deficits. Radiographs and computed tomography (CT) demonstrated calcified intervertebral discs and far lateral extrusion at L6-L7. Magnetic resonance imaging (MRI) confirmed nerve root compression by the extruded disc, without spinal cord compression. Conservative management with gabapentin and methocarbamol for 2 weeks was unsuccessful. Surgical intervention was performed using sequestrectomy, as spinal cord compression was absent on imaging and nerve root compression was isolated, whereby the extruded disc material was removed without bone drilling to preserve segmental stability and minimize operative trauma. The patient showed immediate postoperative neurological improvement, standing on the day of surgery with minimal pain response, and regaining full weight-bearing within 2 days. Postoperative imaging confirmed removal of the compressive disc material, although mild recurrence was observed without neurological deficits. The patient remained pain-free and exhibited continued functional recovery during follow-up. Discussion: This case report is the 1st in veterinary medicine to employ the term "sequestrectomy" and to detail its clinical outcome for the treatment of far lateral IVDE. Conventional surgical options in veterinary practice frequently require partial vertebral resection for decompression, increasing spinal instability, prolonging operative time, and elevating the risk of spinal cord injury; in contrast, sequestrectomy avoids bone drilling and thereby reduces these risks. Although recurrence of disc extrusion remains a concern, human studies have shown comparable recurrence rates between sequestrectomy and conventional discectomy, with superior outcomes in pain and recovery. Furthermore, sequestrectomy preserves the possibility of revision surgery if needed. In this case, patient selection was based on isolated nerve root compression without spinal cord compression and a far lateral fragment that was accessible via a bone-sparing approach. Postoperatively, the patient showed prompt neurological improvement, minimal pain response, and rapid return to full weight‑bearing, with objective gait analysis corroborating functional gains. The successful application of sequestrectomy in this case suggests that it may be a valuable surgical option for select cases of IVDE in veterinary medicine. Future studies are warranted to further evaluate the prognosis and long-term outcomes of this technique, particularly in combination with advanced surgical tools. Keywords: canine, chondrodystrophic breed, IVDE, discectomy, far lateral extrusion, surgery.